Web-based Visual Decision Support System (WVDSS) for letter shop. (February 2017) - Krishnaiyer, Krishnan; Chen, F. Frank
Abstract: Decision Support Systems (DSS) is one of the key tools to transform data to decisions. In this paper, a successful implementation of a web based DSS in a direct mail (letter shop) is explained. Utilizing continuous improvement framework, we provide how the Web-based Visual Decision Support System (WVDSS) helped the organization to successfully turn around the scheduling and capacity planning function along with extending the success to customer service, and warehouse operations. The outcome of implementing the WVDSS were (1) attainment of 100% scheduled delivery date, (2) improved efficiencies across the value stream, and (3) real-time notification of shipment to the customer service representatives. The unique contribution of this work is the original implementation of a web based decision support system in a high variety and low volume letter shop environment spanning transactional and manufacturing value streams. Highlights: Web-based Visual Decision Support System (WVDSS) reduced the scheduling time. It was extended to other departments e.g. quality, customer service, and warehouse. Unique contribution is the original implementation WVDSS in a letter shop. Implementation spanned both transactional and manufacturing value streams. Outcome realized were 100% adherence to the scheduled delivery dates.